Hubungan Inisiasi Menyusu Dini Dengan Keberhasilan ASI Eksklusif - Nurlaeli Nurlaeli; Norma Safitri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Early Initiation of Breastfeeding (IMD) is the process of breastfeeding immediately after birth, with skin-to-skin contact between the mother and baby. Early initiation of breastfeeding is known to play a crucial role in the success of exclusive breastfeeding. However, coverage of early initiation of breastfeeding and exclusive breastfeeding in the community is still suboptimal. This study aims to determine the relationship between early initiation of breastfeeding and the success of exclusive breastfeeding. The research method used was quantitative with an analytical design and a cross-sectional approach. The study sample was mothers with infants aged 6–12 months. Data were collected using a questionnaire and analyzed using the Chi-Square test. The results showed a significant relationship between early initiation of breastfeeding and the success of exclusive breastfeeding (p < 0.05). The conclusion of this study is that mothers who practice early initiation of breastfeeding have a greater chance of successfully providing exclusive breastfeeding.